JUVENILE LIFERS (LETHAL) VIOLENCE, INCARCERATION AND REHABILITATION. - Deegan, Simone (ABINGDON : ROUTLEDGE, 2021)
This book is the first Australian study, based on extensive fieldwork, of the personal backgrounds and processes by which juveniles get drawn into risky and violent situations that culminate in murder. Drawing on interviews with every juvenile under sanction of life imprisonment in the State of South Australia (2015-2019), it investigates links in the chain of events that led to the lethal violence that probably would have been broken had there been appropriate intervention. Specifically, the book asks whether the existing criminal justice frame is the appropriate way to deal with children who commit grave acts. The extent to which prison facilitates and/or inhibits the mental, emotional, and social development of juvenile lifers' is a critical issue. Most - if not all - will be released at some point, with key issues of risk (public protection) and rehabilitation (probability of desistance) coming sharply to the fore. In addition, this book is also the first to capture how significant others including mothers, fathers, grandparents, and siblings are affected when children kill and the level of commitment these relatives have towards supporting the prisoner in his or her quest to build a positive future. Written in a clear and direct style, this book will appeal to students and scholars of criminology, sociology, andpenology; practitioners working in social policy; and all those interested in the lives and backgrounds of juvenile offenders.
OCLC-licensed vendor bibliographic record.
Keywords: Juvenile delinquency -- Australia -- South Australia; Juvenile delinquents -- Rehabilitation -- Australia -- South Australia; Juvenile justice, Administration of -- Australia -- South Australia; Juvenile corrections -- Australia -- South Australia; LAW / Criminal Law / Juvenile Offenders; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Sociology / Marriage & Family